Answer :

Answer:

Step-by-step explanation:

4x - 2y = -2   ------------------(I)

6x + 3y = 27 ------------------(II)

Multiply (I) by 3 & multiply (II) by 2

(I)*3           12x - 6y = -6

(II)*2          12x + 6y = 54  { Now add &  y will be eliminated}

               24x          = 48

 x = 48/24

x = 2

Plugin the value of x in equation (I)

4*2 - 2y = - 2

8 - 2y = -2          {subtract 8 from both side}

-2y = -2 - 8

-2y = -10   {Divide both sides by -2}

y = -10/-2

y = 5

 

Other Questions